Marketing Communication Strategy in Increasing Advertisement Revenue (Case Study on Radio Rau 105 FM Padang Sidimpuan) - Armando Harahap, Hengki Sugeng; Riza, Faisal; Faishal, Muhammad (International Journal of Cultural and Social Science, 2023)
This research is entitled "Marketing Communication Strategy in Increasing Advertising Revenue (Case Study of Radio RAU 105 FM Padang Sidimpuan). The purpose of this study is how the marketing communication strategy is applied to Radio RAU 105 FM Padang Sidimpuan to get increased advertising. The theory used is Communication Theory, Communication Mix Theory and Communication Strategy Theory. This study uses a qualitative research model, namely a descriptive approach. Retrieval of data used is observation, interviews and documentation. This research has seven informants including the person in charge of radio, main director, head of administration and finance, radio broadcaster, advertiser and the public. Based on the research that has been carried out, Radio RAU 105 FM Padang Sidimpuan uses a marketing strategy to increase revenue, especially in advertising. The promotion model used is to carry out social activities to the community, give confidence to business actors by broadcasting featured programs and working with potential advertisers at affordable prices and more flexible confirmation of cooperation. The frequency range of Radio RAU 105 FM Padang Sidimpuan is still limited so that it can influence potential advertisers to work with the radio. Another factor that affects the increase in revenue through advertising is the income of business actors and the economic improvement obtained by business actors.